2017
DOI: 10.1007/s13205-017-0889-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, drug loading and antibacterial activity of nanohydroxyapatite/polycaprolactone (nHA/PCL) electrospun membrane

Abstract: Considering the important factor of bioactive nanohydoxyapatite (nHA) to enhance osteoconductivity or bone-bonding capacity, nHA was incorporated into an electrospun polycaprolactone (PCL) membrane using electrospinning techniques. The viscosity of the PCL and nHA/PCL with different concentrations of nHA was measured and the morphology of the electrospun membranes was compared using a field emission scanning electron microscopy. The water contact angle of the nanofiber determined the wettability of the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 40 publications
(46 reference statements)
5
23
1
Order By: Relevance
“…Whereas the roughness value obtained for the other two PCL/gelatin/P188 composites with 5% and 10% P188 were 679 ± 33 nm and 683 ± 95 nm, respectively. Although the increase in fiber diameter is known to increase the surface roughness [51][52][53], the high roughness of the scaffold with 20% P188 was probably due to increasing in P188 concentration. As 20% P188 based composite scaffold electrospun at 22 kv had the lowest average diameter of 306 ± 163 nm when compared to scaffolds with 10% and 5% P188, which had an average diameter of 327 ± 196 nm and 390 ± 158 nm, respectively ( Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Whereas the roughness value obtained for the other two PCL/gelatin/P188 composites with 5% and 10% P188 were 679 ± 33 nm and 683 ± 95 nm, respectively. Although the increase in fiber diameter is known to increase the surface roughness [51][52][53], the high roughness of the scaffold with 20% P188 was probably due to increasing in P188 concentration. As 20% P188 based composite scaffold electrospun at 22 kv had the lowest average diameter of 306 ± 163 nm when compared to scaffolds with 10% and 5% P188, which had an average diameter of 327 ± 196 nm and 390 ± 158 nm, respectively ( Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…nHA is the major inorganic component of the bone matrix, and its specific affinity toward many adhesive proteins and direct involvement in the bone cell differentiation and mineralization processes make nHA especially appealing for applications in the bone regeneration field [ 62 ]. nHA has been incorporated in PCL by electrospinning in several studies in vitro [ 63 ] and in vivo in a calvarial defect mouse model where association with HA significantly improved bone healing induced by PCL [ 64 ]. The HA-coated PCL membrane has favorable effects on proliferation and differentiation of human periodontal ligament cells and might be a candidate material for periodontal tissue regeneration [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The O─C vibrations of PCL were observed at the absorption peak of 1053, 1018, and 923 cm −1 with the CH 2 vibration appearing at around 809 cm −1 . The ester COO vibrations occur at 1159 and 1238 cm −1 . From these results, it can be concluded that the CQ‐PCL NPs loaded CS/Col/HA was successfully incorporated into the scaffolds.…”
Section: Resultsmentioning
confidence: 75%